Deviasi Hukum dalam Perjanjian Bisnis yang Menyampingkan Ketentuan Pasal 1266 dan Pasal 1267 KUH Perdata - Azkannasabi, Muhammad; Iskandar, Hardian (Journal of Economic and Business Law Review, 2024)
A contract that contains an agreement that contains the rights and obligations that must be carried out by the parties in a business is called a business agreement. Failure to fulfill one of the obligations of the parties to the agreement does not automatically terminate the agreement, but this termination must go through a court process as determined by Article 1266 and Article 1267 of the Civil Code. However, in practice, in agreements, there are many clauses that override the two articles because according to business people, these articles are difficult to apply in a business agreement. This has received special attention from legal experts, practitioners, and judges. In this case, there is a dissenting opinion regarding the waiver of articles 1266 and 1267 of the Civil Code, the first of which they argue that the waiver is acceptable because of the principle of freedom of contract and believes that the provisions in book III of the Civil Code are trapping provisions. Meanwhile, some other opinions do not accept the waiver because they believe that the provisions in book III of the Civil Code are mandatory provisions. Based on the principle of pacta sund servanda, the binding force in an agreement that contains a clause of nullity conditions that override articles 1266 and 1267 of the Civil Code is in solidarity and mutual trust to override the article which applies as a law by the parties who determine it earlier.